Relation Between the Sense of Coherence and the System of Values in People eith Eating Disorders - Anna Wiatrowska (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
The article presents results of studies on the relations between the sense of coherence and the system of values in people with eating disorders. The study makes use of the Life Orientation Questionnaire (SOC-29) by Antonovsky and the Portrait Value Questionnaire (PVQ-R2) by Schwartz. The studies were conducted in groups of people with eating disorders and healthy ones. Significant differentiation occurred in all dimensions and the general result of the sense of coherence and the system of values. The analyses partially confirmed the hypothetical assumptions concerning the relation between the sense of coherence and the system of values in the studied people. The obtained results can provide the basis of studies concerning the relation between the analyzed variables and the forms of eating disorders.